The effect of two different oral antiseptics on dental plaque formation (De Novo Biofilm) and on gingival inflammation - Zelić Obrad; Čakić Saša; Luković Natalija (Srpski Arhiv za Celokupno Lekarstvo, 2009)
Introduction. Since the discovery that periodontal diseases are caused by microbial plaque the interest of many scientists has been focused on oral antiseptics. There are very few mouthrinses with oral antiseptic effect originally designed in our country. One of these is Ozosept® solution. Objective. This study evaluated the effect of Ozosept® solution (phenol compound) on the oral hygiene and gingival inflammation, in comparison with Hibidex DAP® solution (chlorhexidine digluconate). Methods. Two groups, each of 21 persons, which did not significantly differ concerning Silness-Löe plaque index (PI) and Löe-Sillnes gingival index (GI), used one of the studied oral antiseptic for a 15-day period. Oral hygiene was maintained by subjects' habitual home methods, and no technique of professionally advised brushing was performed during the experimental period. Results. At the end of the study, PI and GI scores were lowered to a statistically high significance in both groups of participants in comparison to the indexes at the beginning of the study. At the end of the study, PI and GI scores did not significantly differ between the two analyzed groups. No side effects, which were recorded in the Hibidex DAP® group (tooth and filling staining 9.5% and 4.74% respectively, transitory tongue numbness 28.6% and reduced taste sensation 14.3%), were registered in the group of subjects using Ozosept® solution. Conclusion. It is concluded that Ozosept® solution is effective in the control of dental plaque - biofilm accumulation and gingival inflammation, and produces no side effects related to chlorhexidine digluconate usage.